PERAN BHABINKAMTIBMAS MENGURANGI KEJAHATAN YANG DILAKUKAN OLEH REMAJA DI KABUPATEN PINRANG - Muh Fadli Faisal Rasyid (Jurnal Delik ADPERTISI, 2023)
The purpose of this study was to determine the role of Bhabinkamtibmas in reducing crimes committed by adolescents in Pinrang District and to find out the obstacles handled by Bhabinkamtibmas in reducing crimes committed by adolescents in Pinrang District. The research approach in this study is normative and empirical. Normative is research conducted by reviewing and analyzing the substance of laws and regulations on basic issues or legal issues in consistency with existing legal principles. Juridical research conducted in the field, in order to obtain concrete data in accordance with what is happening in society and related to criminal acts. While the Empirical Approach is carried out to find out the actual condition of the field by conducting interviews with several field informants. The results of this study reveal that the role of Bhabinkamtibmas in Pinrang Regency is to reduce crimes committed by teenagers by carrying out counseling activities to convey messages about the dangers of making acquaintances with teenagers and providing motivation to take positive actions to create security and comfort for the community. On the other hand, the obstacles faced by Bhabinkamtibmas Pinrang Regency are the lack of coordination between parents of teenagers and the lack of resources for Bhabinkamtibmas Pinrang Regency.